THE EFFORTS OF THE SURAKARTA POLICE KAMSEL UNITS IN TRAFFIC ACCIDENT PREVENTION TO ACHIEVE KAMSELTIBCARLANTAS - Gumelar Rizki Duana (Police Studies Review, 2022)
Kamseltibcarlantas which stands for security, safety, order, and smooth traffic is a situation where traffic users feel good, and feel safe, free from fear of the threat of obstacles or disturbances. Kamseltibcarlantas in Surakarta has not been realized due to the high number of accidents, this study aims to find out how the efforts, and cooperation of the Surakarta Police Kamsel Unit in preventing traffic accidents to realize Kamseltibcarlantas. The approach chosen in this paper uses a qualitative approach. The reason the author took qualitative is to be able to see more deeply about social phenomena that occur in the field and to be able to provide problem-solving to find the efforts that have been carried out. And, so that the author can explain the results of writing and can explain the urgency of this writing. Based on the results of interviews, observations, and data processing at the Kamsel Unit of the Surakarta Police, it was found that there was a shortage of human resources, the absence of personnel conducting Dikjur/Dikbang, lack of budget, unbalanced Dikmas following the Head of Police's Juklak on Dikmas, and poor condition of facilities and infrastructure as well as support. owned by the Unit Kamsel Polresta Surakarta. Based on the results of the study, it was concluded that Kamseltibcarlantas had not been realized due to the lack of optimal accident prevention efforts by the Kamsel Unit caused by internal factors, namely human resources, budget, methods, and infrastructure as well as external factors including the lack of APILL on Surakarta roads, poor lighting, unorderly parking locations. , and the situation of the Surakarta area. So the Surakarta Police Kamsel Unit needs to optimize efforts to prevent traffic accidents.